'And' and 'But': A Note1. (19th April 2017) - Kripke, Saul A.
Abstract : Most philosophers seem to be under a misleading impression about the difference between 'and' and 'but'. They hold that they are truth‐functional equivalents but that 'but' adds a Gricean 'conventional implicature' to 'and'. Frege thought that the implicature attached to 'but' was that the second clause is unlikely given the first; others have simply said they express a contrast between the two. Though the second formulation may seem more general, in practice writers seem to agree with Frege's idea. The present note will argue against this conventional view. Indeed, 'and' and 'but' may both convey conflicting implicatures; and the traditional characterization of the implicature of 'but' is outright mistaken, or at least misleading.